Do Biophilic Atmosphere, Convenience and Accessibility Encourage Intention to Visit with Mediation of Visitor’s Affective States? (Case Study: The Breeze BSD City Mall) - Andria, Sukma; Salim, Lina (Ekonomi Bisnis, 2024)
This study aims to determine the effect of biophilic atmosphere and convenience and accessibility on intention to visit with affective states as the mediation of the Breeze BSD City. The Breeze BSD City is one of the malls that applies the concept of a biophilic atmosphere and provides convenience and accessibility. The research object is The Breeze mall located in Tangerang, Indonesia. Empirical data was collected using non-probability method of purposive sampling technique with a total of 210 respondents. Empirical data was processed used the Structural Equation Model (SEM) technique and the Smart Partial Least Square (PLS) 3 analysis instrument. This study proposed seven (7) hypotheses and six (6) hypotheses were accepted. The results of the analysis showed that convenience and accessibility have a direct and indirect effect on the intention to visit by affective states as a mediator. Convenience and accessibility also have a direct and significant effect on affective states. Biophilic atmosphere has no direct effect on intention to visit but has an indirect effect on intention to visit by affective states as a mediator. Meanwhile, the biophilic atmosphere also has a significant direct effect on affective states and affective states have a direct influence on the intention to visit.